Tryptic digestion of spectrin in variants of hereditary elliptocytosis. - Coetzer, T (1981)
Spectrin, either in the form of unfractionated low ionic strength extracts of erythrocyte membranes or purified by chromatography on Sepharose (CL)4B, was subjected to tryptic digestion at 0 degrees C. Four patients, each with a different variant of hereditary elliptocytosis, were studied. In one patient, whose erythrocytes showed significant fragmentation on heating on 45 degrees C, such preparations generated a remarkably different pattern of polypeptide fragments on tryptic digestion at low ionic strength. In this patient 32P was released at a slower rate on tryptic digestion of labeled band 2, and an unusual 32P-labeled peptide fragment was also generated, in contrast to control preparations in which such a peptide could not be easily distinguished. There was increased susceptibility of this patient's spectrin to tryptic digestion at physiological ionic strength, but the qualitative pattern of polypeptide fragments was normal. Phosphorylation of spectrin by membrane protein kinase was markedly impaired in this patient, whereas phosphorylation of casein ws unimpaired. However, the phosphorylation of spectrin in her intact erythrocytes was normal. Our findings suggest an abnormality of spectrin structure which we postulate is causally related to the predisposition to hemolysis in this patient, but do not distinguish whether this is a primary abnormality or a post-translational modification of the spectrin molecule. The other three patients showed normal tryptic digestion of spectrin.